MUSEUM PERJUANGAN TRIDAYA EKA DHARMA DAN LITERASI SEJARAH DI BUKITTINGGI, 1973-2018 - Ayu Rahma; Suriani (ADISAM PUBLISHER, 2023)
The Tridaya Eka DharmaStruggle Museum, which is located in Bukittinggi, is more unique than the others.The uniqueness of this museum is that there is a plane displayed in the museum yard and to the right and left of the plane there is a cannon facing the road. The type of writing in this research uses a historical research method, namely descriptive narrative (qualitative), namely providing an overview and eksplanation of the Tridaya Eka DharmaStruggle Museum and Historical Literacy in Bukittinggi (1973-2018). In this research, the primary sources are objects from museum collections, documents and also written works that discuss the Tridaya Eka Dharma struggle museum. Apart from that, the authors also conducted interviews with officers who look after and manage the museum. The results of the research that has been carried out explain that the development and use of the Fridaya Eka Dharma struggle museum from 1973-2018 has undergone changes. The objects maintained in this museum are silent witnesses to the occurrence of colonialism in Indonesia and the efforts of fighters and the TNI to seize power and maintain independence. The Republic of Indonesia from the colonial rule of foreign troopsKeywords Historical LiteracyDevelopment, Utilization, Tridaya Eka Dharma Struggle Museum,Abstract